Multifunctional PDO Thread Coated with Mg(OH)2/ZnO Nanoparticles and Asiaticoside for Improved Facial Lifting - Dong Min Kim; Seung-Woon Baek; Jeong Min Park; Da-Seul Kim; Semi Lee; Jun-Kyu Lee; Chun Gwon Park; Dong Keun Han (MDPI AG, 2023)
As interest in skin aesthetics increases, treatments to suppress aging are increasing. Among them, a facelift is the most effective procedure for improving wrinkles. However, side effects including inflammatory reactions occur due to the limitations of the PDO thread itself used during the procedure. In this paper, to improve the function of PDO thread, inorganic particles such as magnesium hydroxide (MH) and zinc oxide (ZO) and a biologically active agent, asiaticoside, were coated on the surface of PDO thread using ultrasonic coating technology. The coated thread exhibited excellent biocompatibility, promoted collagen synthesis, reduced inflammation, and stimulated angiogenesis in vitro and in vivo. The multifunctional PDO thread has shown promising potential for skin regeneration without inducing fibrosis. Such a practical coating system and the developed multifunctional PDO thread suggest new possibilities for developing safer and more effective materials in cosmetic and regenerative medicine to prevent aging and improve skin aesthetics.